Relations Between Class Competition and Primary School Students’ Academic Achievement: Learning Anxiety and Learning Engagement as Mediators - Li, Guoqiang; Li, Zhiyuan; Wu, Xinyue; Zhen, Rui (Frontiers in Psychology, 2022)
This study aimed to analyze the relationship between class competition and primary school students’ academic achievement, considering the possible mediating role of learning anxiety and learning engagement. Participants were 1479 primary school students from four primary schools in Zhejiang, China. We analyzed participants’ scores for class competition, learning anxiety, and learning engagement and their last two final exam scores. Class competition did not directly predict academic achievement, but indirectly affected academic achievement through learning anxiety and learning engagement. There were three effect paths: (1) class competition negatively predicted academic achievement by increasing learning anxiety; (2) class competition positively predicted academic achievement by promoting learning engagement; and (3) class competition affected academic achievement through multiple mediating effects of learning anxiety and learning engagement. This study highlights the important roles of learning anxiety and learning engagement in class competition and academic achievement, which have theoretical and practical significance.